Traumatism in the Wild Animals Kept and Offered at Predynastic Hierakonpolis, Upper Egypt. (24th March 2015) - Van Neer, W.; Udrescu, M.; Linseele, V.; De Cupere, B.; Friedman, R.
Abstract: A description is given of the violence‐related pathologies that are observed in a number of wild mammals that were buried in the predynastic cemetery HK6 at Hierakonpolis, Upper Egypt. Unlike other predynastic graveyards, where only domestic cattle, sheep, goat and dogs are interred, the elite cemetery HK6 yielded also a wide variety of wild species that were buried as part of extensive mortuary complexes surrounding the graves of the highest local elite. The animals were interred, singly or in groups, often in graves of their own, but some also accompany human burials. Pathologies were found on the skeletons of 20 of the 38 wild animals discovered thus far, namely 15 anubis baboons ( Papio anubis ), one leopard ( Panthera pardus ), one jungle cat ( Felis chaus ), one hartebeest ( Alcelaphus buselaphus ), one aurochs ( Bos primigenius ) and one hippo ( Hippopotamus amphibius ). Most of the pathologies are healed fractures resulting from violent blows, and a smaller proportion seems to be related to tethering. These conditions indicate that the animals were held in captivity for a prolonged period of time after their capture. The type and frequency of the encountered deformations differ from those seen in wild animals from other, more recent Egyptian cemeteries (Abydos, Tuna el‐Gebel, Gabanet el‐Girou and Saqqara) where mainly metabolic disorders are observed that have been attributed to chronic malnutrition and vitamin D deficiency as a result of inadequate housing in a dark environment. Copyright © 2015 John Wiley & Sons, Ltd.